2017
DOI: 10.3389/fnagi.2017.00314
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Innovation and Underlying Neural Mechanisms Via Cognitive Training in Healthy Older Adults

Abstract: Non-invasive interventions, such as cognitive training (CT) and physical exercise, are gaining momentum as ways to augment both cognitive and brain function throughout life. One of the most fundamental yet little studied aspects of human cognition is innovative thinking, especially in older adults. In this study, we utilize a measure of innovative cognition that examines both the quantity and quality of abstracted interpretations. This randomized pilot trial in cognitively normal adults (56–75 years) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…There is a significant body of literature on functional activity and connectivity changes after strategy-based CT that show similar findings as the results from this review. For instance, mnemonic strategy CTs increased activity of fronto-parietal and temporal regions in individuals suffering from MCI and increased functional connectivity within cognitive networks in healthy elderly (Chapman et al, 2015;Chapman, Spence, Aslan, & Keebler, 2017;Hampstead, Stringer, Stilla, Giddens, & Sathian, 2012;Hampstead, Stringer, Stilla, & Sathian, 2019;Simon et al, 2019). These studies were, however, beyond the scope of this review.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 91%
“…There is a significant body of literature on functional activity and connectivity changes after strategy-based CT that show similar findings as the results from this review. For instance, mnemonic strategy CTs increased activity of fronto-parietal and temporal regions in individuals suffering from MCI and increased functional connectivity within cognitive networks in healthy elderly (Chapman et al, 2015;Chapman, Spence, Aslan, & Keebler, 2017;Hampstead, Stringer, Stilla, Giddens, & Sathian, 2012;Hampstead, Stringer, Stilla, & Sathian, 2019;Simon et al, 2019). These studies were, however, beyond the scope of this review.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 91%
“…All the other studies report effects on cognitive function, on brain structure/function, or on both. In addition, in seven studies listed in Table 6 (four using MRI, 66 , 67 , 78 , 79 one using positron emission tomography, 77 one using electroencephalogram, 79 and one examining serum brain-derived neurotrophic factor [BDNF] 69 ) that included groups undergoing single physical training (not combined with other kinds of training), positive effects of physical training on cognition and on brain structure or function were reported. Concerning cognition, improvements were especially observed for short-term 59 , 60 and working memory, 53 long-term immediate and delayed memory, 60 attention, 61 , 62 and executive functions.…”
Section: Specific Impact Of Cognitive and Physical Training On Cognitmentioning
confidence: 99%
“…Concerning cognition, improvements were especially observed for short-term 59 , 60 and working memory, 53 long-term immediate and delayed memory, 60 attention, 61 , 62 and executive functions. 63 On the brain level: 1) structural changes have been found in both white 53 , 59 and gray matter, 64 , 65 and 2) functional changes have been observed at the level of functional connectivity, 53 , 59 CBF, 60 , 66 , 67 and task-related pattern of blood oxygen level dependent response. 17 , 68 Some authors 61 suggested that the thickening of the gray matter might be due to an increase in the level of BDNF.…”
Section: Specific Impact Of Cognitive and Physical Training On Cognitmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, SMART focuses on many of the cognitive domains that are key to cognitive readiness. In multiple clinical trials, SMART has shown to improve mental agility, strategic learning, problem solving, focus, and psychological well-being [ [12] , [13] , [14] , [15] , [16] , [17] ]. The SMART protocol has been shown to be superior to cognitive training of the same duration and dose of treatment [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%